Edward S. Curtis and the Complex Legacy of The North American Indian Project - Rokosz, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
In 1907 Edward S. Curtis published the first volume of The North American Indian – the 20-volume series which was his life achievement, completed in 1930. During thirty years he took probably about 40,000 photographs of Native Americans belonging to various tribes. These included both portraits and depictions of everyday life of the peoples his generation believed were vanishing. During the field work he also collected textual material documenting the tribes’ histories, legends, rituals as well as biographies of individual people. The project, in its immensity, exhausted the resources and did bring Curtis the recognition he hoped for. His works were rediscovered in 1972 and since then photographs have been either criticised for being staged and not depicting the Native tribes’ life as it really was, or appreciated both for their aesthetic quality and documentary value. The article provides an overview of the project, discusses the controversies surrounding it and its significance from today’s perspective. It also refers to the legacy of Curtis’s work and the way contemporary artists remain in a dialogue with it.

W 1907 r. amerykański fotograf Edward S. Curtis opublikował pierwszy tom dzieła The North American Indian – 20-tomowej serii ukończonej w 1930 r., opisującej i ilustrującej życie 80 plemion żyjących w zachodniej części Stanów Zjednoczonych. Przez trzydzieści lat Curtis wykonał prawdopodobnie około 40 tysięcy fotografii Indian amerykańskich i zgromadził ogromny materiał etnograficzny dotyczący codziennego życia plemion, ich legend, mitów, historii. Wykonane zdjęcia to zarówno portrety, jak i przedstawienia różnego typu zajęć przedstawicieli „znikającej rasy”, jak postrzegano na początku wieku rdzennych mieszkańców kontynentu. Projekt został ukończony ogromnym kosztem i nie przyniósł Curtisowi doczesnej sławy. Jego prace zostały odkryte na nowo w 1972 r. i od tego czasu są zarówno krytykowane za zafałszowywanie rzeczywistości oraz niewielką wartość dokumentalną, jak i doceniane za walory estetyczne i sam fakt zaistnienia, umożliwiający potomkom zobaczenie swoich odległych przodków. Artykuł omawia założenia projektu, jego efekty, źródła kontrowersji, a także współczesne znaczenie kulturowe tego ogromnego i jedynego w swoim rodzaju przedsięwzięcia.
Edward S. Curtis i złożoność dziedzictwa jego projektu pt. The North American Indian
Keywords: Edward S. Curtis; The North American Indian; Native Americans; history of American photography; ethnography; rdzenni mieszkańcy Ameryki Północnej; Indianie amerykańscy; historia amerykańskiej fotografii; etnografia